Analyses of p53 expression pattern and BRCA mutations in patients with double primary breast and ovarian cancer. Issue 2 (1st February 2004) - Bruchim, I.; Fishman, A.; Friedman, E.; Goldberg, I.; Chetrit, A.; Barshack, I.; Dekel, E.; Hirsh-Yechezkel, G.; Modan, B.; Kopolovic, J.
Abstract : Objective: To analyze the somatic pattern of p53 expression and BRCA germline mutation status in Israeli patients with both ovarian (OvCa) and breast cancer (BrCa). Methods: The study group comprised 43 Israeli patients with OvCa, all of whom had previous primary BrCa. p53 immunohistochemistry (IHC) on all available archival tissues and genotyping for the three predominant Jewish germline BRCA1–2 mutations were carried out. Samples from 64 patients with solitary OvCa and 61 with solitary BrCa were similarly analyzed as controls. Results: p53 expression pattern and the immunopositivity rate were similar in the ovarian and breast tumors within the study group and in the two control groups: positive p53 staining was detected in 68% of ovarian tumors in the study group compared with 71.9% in the controls, and in 19.4% of the BrCa tissues versus 21.3% in the controls. Within the study group, advanced stage OvCa had a higher rate of p53 expression (84%) compared to early stage disease (38.5%) ( P = 0.006). This difference was not apparent in the solitary OvCa control group. OvCa in BRCA1–2 mutation carriers from the study group were more likely to display positive p53 staining (79%), especially in tumors diagnosed before the age of 60 (90%) compared with the OvCa of noncarriers (60%), but this difference was statistically insignificant. The p53 expression rate in BrCa samples from the study group was not associated with BRCA1–2 mutation status. Conclusions: Positive p53 expression, detected by IHC, in OvCa patients with previous primary BrCa is significantly higher in advanced stage disease in BRCA1–2 mutation carriers. There is a higher positive p53 expression somatically in OvCa in BRCA1–2 carriers in whom OvCa was diagnosed before the age of 60 years, although this trend is not statistically significant. These observations suggest that somatic p53 inactivation may be an important event in ovarian tumorigenesis in this subset of patients.